KLASIFIKASI VOLATILITAS HARGA DAGING AYAM DAN CABE RAWIT MERAH DENGAN DECISION TREE - Mohamad Hegar Sukmana Wibowo; Muhammad Din Al Ayubi; Elkin Rilvani (Jurnal Komputer dan Teknologi, 2025)
Price fluctuations of key food commodities such as chicken meat and red bird’s eye chili exhibit significant volatility patterns in Bekasi Regency, impacting consumers, producers, and local government authorities. This study aims to classify the level of price volatility for these two commodities using the Decision Tree C4.5 algorithm. Daily price data for the year 2024 were obtained from the Department of Communication, Informatics, Cryptography, and Statistics of Bekasi Regency, then processed and analyzed using RapidMiner with an 80:20 training-to-testing data ratio. The classification results show that the C4.5 algorithm achieved an accuracy of 93.84% for chicken meat prices and 80.56% for red chili prices. These findings demonstrate the effectiveness of the C4.5 algorithm in recognizing price volatility patterns and its potential in supporting decision-making for regional price monitoring systems and early warning mechanisms for market shocks. This research offers practical contributions to government efforts in price stabilization.